Corrosion Inhibition of Aluminum Alloy in 50% Ethylene Glycol Solution - Rassoul, G. A.; M. Kassim, Dhia El-Din; H. EsSebbagh, Baseem (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The present study was conducted to evaluate the effect of different inhibitors on the corrosion rate of aluminum in 50% (v/v) ethylene glycol solution at 80°C and pH 8.0 in which the electrochemical technique of linear sweep voltammetry was employed to characterize each inhibitor function and to calculate the corrosion rate from Tafel plots generated by a computer assisted potentiostat. It is found that both sodium dichromate and borax reduces the corrosion rate by polarizing the anodic polarization curve while sodium phosphate, potassium phosphate, and sodium benzoate reduces the corrosion rate by polarizing both the anodic and cathodic polarization curve. When inhibitor concentration increases from I g/l up to 3 g/l, the inhibitor efficiency increases from 50% up to 85% for borax, from 64% up to 71% for sodium dichromate, and from 66% up to 82% for sodium phosphate, while constant inhibitor efficiency of about 55% and 50%for potassium phosphate and sodium benzoate were obtained respectively.